Plasma-activated Water: Mechanisms of the activationand Its Physico-Chemical Properties - Arda, Gede; Shoodiqin, Dian Mart (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
<article class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:fae0572e-2e95-430f-987d-0f9e7639e3e5-29" data-testid="conversation-turn-60" data-scroll-anchor="true" data-turn="assistant"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="7a00b81e-00cc-4763-863b-e991f895116d" data-message-model-slug="gpt-5-mini"> Plasma technology has been recently developed due to its unique properties and potential applications across various fields. Plasma is a gas whose constituent molecules are dissociated and exhibit reactive properties. However, because of these properties, plasma must be used immediately after generation. Activating water with plasma makes the water more reactive, allowing it to be utilized similarly to plasma in gas form. This literature review presents water activation technology using plasma, focusing on the generation mechanism and the accompanying reactions. The article also introduces plasma technology, which is currently minimally studied in Indonesia.